Human B‐cell memory is shaped by age‐ and tissue‐specific T‐independent and GC‐dependent events. Issue 2 (14th December 2016) - Aranburu, Alaitz; Piano Mortari, Eva; Baban, Anwar; Giorda, Ezio; Cascioli, Simona; Marcellini, Valentina; Scarsella, Marco; Ceccarelli, Sara; Corbelli, Sandro; Cantarutti, Nicoletta; De Vito, Rita; Inserra, Alessandro; et al.
Abstract : The evolution of the B‐cell memory pool from infancy to adulthood. Although switched memory B cells are always generated in the germinal center (GC), there are three types of IgM memory B cells: innate, remodeled, and GC‐derived. Shaping of the innate memory repertoire occurs in the GC with age. Abstract : Switched and IgM memory B cells execute different and noninterchangeable functions. We studied memory B cells in children of different ages, in peripheral blood and spleen and compared them with those of children born asplenic or unable to build germinal centers. We show that, whereas switched memory B cells are mostly generated in the germinal centers at all ages, IgM memory B cells can be distinct in three types with different developmental history. Innate IgM memory B cells, the largest pool in infants, are generated in the spleen by a germinal center‐independent mechanism. With age, if the spleen is present and germinal centers are functional, innate IgM memory B cells are remodelled and accumulate somatic mutations. The third type of IgM memory B cell is a by‐product of the germinal center reaction. Our data suggest that the B‐cell memory developmental program is implemented during the first 5–6 years of life.